Strategies for Increasing Indonesian Halal Product Exports - Muhtadi; Saharuddin, Desmadi; Aisyah, Muniati; Sofyan Rizal (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
This research examines the strategies for increasing Indonesian Halal Product Exports by the implementation of Code 952 by the Directorate General of Customs and Excise (DGCE). Using a qualitative method, this research analyzes the strategies to optimize the growth of national halal product exports by the implementation of Code 952, including challenges faced. The results show that its strategies including 1) improve the accuracy of halal product export data, and 2) support the development of the national halal industry. The use of Code 952 has shown positive developments, with an increase in the number of Export Declarations (PEB) that include this code. However, challenges remain in its implementation, particularly regarding exporter compliance and inter-agency coordination. Recommended optimization strategies include increasing socialization and education for exporters, strengthening coordination between relevant agencies, developing incentives for compliant exporters, improving information technology system capacity, and developing more aggressive marketing strategies for Indonesian halal products in the global market. The implementation of Code 952 aligns with the government’s efforts to make Indonesia a world center for halal producers and is expected to enhance the competitiveness of Indonesian halal products in the global market.